Effects of Ionizing Radiation on the Capacity of Escherichia coli to Support Bacteriophage T4 Growth - Marsden, Howard (1972)
The loss in capacity of irradiated bacteria to support the growth of T4 phage has been studied for two strains, Escherichia coli B and E. coli B(s—1). Following a dose of 25 krads, the capacity is quite rapidly lost during postirradiation incubation so that after two hr of such incubation at 37 C only 12% remains in strain B and 3% in strain B(s—1). Evidence that capacity is lost in an all-or-none fashion was provided by two types of experiments: (i) a single-burst analysis of those cells which survived to give a burst, and (ii) an analysis of the regulation of an early phage enzyme. Several processes were examined to try to determine the cause of the loss in capacity. These were the ability of the irradiated and postirradiation incubated cells to respire, to allow phage adsorption and injection of phage deoxyribonucleic acid, to support the transcription and translation of an early gene, and to support replication of phage deoxyribonucleic acid. Of these processes, transcription and translation appeared to be the most closely associated with the capacity loss, although respiration was reduced to 50% after 2 hr.